Creating Sustainable Products - Ries, Lena; Wartzack, Sandro; Zipse, Oliver (Road to Net Zero, 2023)
On the Road to Net Zero, products must not only become CO2-neutral in the consumption phase, but the environmental impact needs to be mitigated from the extraction of the raw materials to their end-of-life disposal. The consideration of the entire life cycle—cradle to cradle—as well as rising consumer demand for sustainable products—requires a new paradigm in product design: Design for circularity. Circular design focuses on developing design strategies that enable circularity, such as material selection, design for disassembly, product lifetime extension strategies, and the design of closed-loop systems. Thus, the first section after the introduction of this chapter (Sect. 5.2) provides an overview of the research field of design for circularity. After reviewing the concept of the circular economy (CE), different frameworks for operationalizing the CE are outlined. Based on this review and discussion, we derive three implications for circular design: a change in product design, a change in service design, and a change in user behavior. Finally, we address the implementation challenges that manufacturing companies face when transitioning to a CE. In the subsequent expert discussion (Sect. 5.3) between Oliver Zipse and Prof.-Ing. Sandro Wartzack, these issues are reflected upon from a practitioner’s perspective. In the final section of this chapter (Sect. 5.4), future avenues of research are presented, and the challenges and opportunities of circular design strategies are discussed.<br
Keywords: Design for circularity; Circular economy; R-strategies; Product life cycle; Product service systems